Explaining the growth of CSR within OECD countries: The role of institutional legitimacy in resolving the institutional mirror vs. substitute debate - Daniel Kinderman; Mark Lutter (Max Planck Institute for the Study of Societies, 2018)
Two strands of literature have emerged to explain the rise of a new form of private governance, Corporate Social Responsibility (CSR). One camp argues that CSR expansion is likely during periods of economic liberalization because CSR tends to substitute for growing institutional voids and a lack of social regulation. The other camp argues that CSR is likely to diffuse within coordinated economies because it mirrors these institutional settings. While both camps find empirical support for their arguments, no one has yet managed to combine both perspectives. In our study, we develop three hypotheses based on two (rationalist and constructivist/sociological) strands of institutional theory. Based on a new dataset comprising the corporate membership in business-led CSR organizations in over thirty countries from 1981 to 2008, we show that economic liberalization has a strong effect on CSR expansion when the legitimacy of CSR is low. However, when the practice has achieved substantial cultural acceptance, economic liberalization no longer drives CSR expansion. In this setting, CSR expansion is most likely to occur within socially regulated economic contexts. – – Es haben sich zwei Forschungsansätze etabliert, die das Aufkommen neuer Formen privater Steuerung, der Corporate Social Responsibility (CSR), erklären wollen. Der erste Ansatz argumentiert, dass die Ausbreitung von CSR mit ökonomischer Liberalisierung einhergeht, weil CSR als ein willkommener Ersatz für soziale Deregulierung fungiert. Der zweite Ansatz argumentiert, dass sich CSR eher in koordinierten Marktökonomien ausbreitet, weil es die dortigen institutionellen Settings spiegelt. Obwohl beide Richtungen empirische Evidenz für ihre Argumentation liefern, hat niemand bislang beide Sichtweisen zu integrieren versucht. In diesem Beitrag entwickeln wir drei Hypothesen, die auf zwei Ansätzen der Institutionentheorie beruhen (rationale vs. konstruktivistische bzw. soziologische Ansätze). Auf Grundlage eines Datensatzes, der die Mitgliedschaften von Unternehmen in CSR-Organisationen in mehr als dreißig Ländern zwischen 1980 und 2008 erfasst, zeigen wir, dass ökonomische Liberalisierung einen besonders starken Effekt auf die Ausbreitung von CSR hat, wenn die Legitimität des CSR gering ist. Hat die Praxis des CSR jedoch eine größere kulturelle Akzeptanz erlangt, geht die weitere Ausbreitung der Praxis nicht länger mit ökonomischer Liberalisierung einher. Nur in dieser Situation ist die Ausbreitung von CSR als Spiegelung des institutionellen Settings koordinierter Marktökonomien zu betrachten.
hdl:21.11116/0000-0000-CD00-9
Keywords: 300; corporate social responsibility; diffusion; institutions; legitimacy; liberalization; membership; privatization; neo-institutionalism; Institutionen; Legitimität; Liberalisierung; Privatisierung; Neo-Institutionalismus